2020
DOI: 10.1155/2020/6504260
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive-Type Jaundice without Bile Duct Dilatation in Generalized Peritonitis Is a Specific Sign of Spontaneous Gall Bladder Perforation

Abstract: Generalized peritonitis caused by spontaneous gall bladder perforation is rare and difficult to diagnose preoperatively. The increased absorption of the spilling conjugated bile from the gall bladder by the inflamed peritoneum causes jaundice and direct hyperbilirubinemia. A 56-year-old male patient with septic generalized peritonitis and obstructive-type hyperbilirubinemia came to our hospital. The blood examination showed that total, direct, and indirect bilirubin were 6.20, 5.38, and 0.82 mg/dl. The gall bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The presumptive diagnosis of gall bladder perforation is a challenge when patient presents with features of sepsis and imaging modalities such as ultrasonography, CT scan, MRCP are also inconclusive [ 4 ]. The HIDA scan which is more sensitive to diagnose gall bladder perforation is also not useful in case of septic patients as in our case [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presumptive diagnosis of gall bladder perforation is a challenge when patient presents with features of sepsis and imaging modalities such as ultrasonography, CT scan, MRCP are also inconclusive [ 4 ]. The HIDA scan which is more sensitive to diagnose gall bladder perforation is also not useful in case of septic patients as in our case [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis with medical and surgical management might lower the morbidity and mortality associated with the condition. However, the diagnosis of gall bladder perforation is often a challenge when imaging techniques such as ultrasonogram (US), computed tomography (CT) scan, hepatobiliary iminodiacetic acid (HIDA) scan and magnetic resonance cholangiopancreatography (MRCP) are inconclusive [ 3 , 4 ]. Moreover, it becomes even difficult when the patient has presented after perforation and with nonspecific signs and symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Another rare cause of generalized peritonitis is gallbladder perforation. 3 In addition, almost half of the cIAI cases at Dr. Soetomo Hospital Surabaya had developed sepsis. A previous study in Indonesia also reported that gastric perforation might lead to sepsis or severe sepsis.…”
Section: Introductionmentioning
confidence: 99%